A course in farm mechanics for Pittsfield, Illinois, community high school - Proctor, Phil W., author; Schmidt, Gustavus Adolphus, 1880-, advisor; Henry, George F., committee member; Anderson, Clarence S., committee member; Howard, Carl G., committee member; Avery, George T., committee member (Colorado State University. Libraries, 1941)
To view the abstract, please see the full text of the document.
Keywords: Agricultural machinery; Agricultural education -- Illinois -- Pittsfield; Agriculture -- Study and teaching